Collective Impact of Entrepreneurial Self-Efficacy and Risk Propensity on Entrepreneurial Intentions; Mediating Role of Perceived Social Support - Khalid, Arusa; Bashir, Mohsin; Saqib, Shahnawaz (International Journal of Engineering and Technology, 2018)
In order to extend the discussion of entrepreneurship, this empirical study has indicated the crucial impact of entrepreneurial self-efficacy on entrepreneurial intentions of a person, while this relation is being moderated by ability based approach of emotional intelligence. Our findings have indicated the extent to which the students of business studies remain successful in exploring market opportunities and will turn into successful entrepreneurs under the umbrella of emotional Intelligence .Moreover it has also elucidated the influence of perceived social support in persuading self-employment. The sample of 260 business Students was taken from Pakistan. Research findings helped students witnessing those depicting higher level of emotional intelligence are more willing to take and tolerate risks and are eager to start up their own businesses .Results also revealed that risk propensity has moderate effects on entrepreneurial intentions. Implications are also being discussed for clear understanding of vitality of discussion.Â Â